2019
DOI: 10.1097/pr9.0000000000000710
|View full text |Cite
|
Sign up to set email alerts
|

Social support buffers the negative influence of perceived injustice on pain interference in people living with HIV and chronic pain

Abstract: Introduction: A growing literature attests to the overwhelming prevalence of disabling chronic pain among people living with HIV (PLWH), yet very little is known about psychosocial contributors to poor chronic pain outcomes in this population. Pain-related perception of injustice may promote pain interference by hindering engagement in daily activities among individuals with chronic pain. Social support has been shown to buffer the negative impact of harmful beliefs on well-being and facilitate ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The study by Penn et al in this issue brings needed attention to the psychosocial context of chronic pain in people living with HIV (PLWH) in the current treatment era. 17 As PLWH age and have normal life expectancy with antiretroviral therapy (ART), quality of life is now a focus. 9,15 Chronic pain, as highlighted by Penn et al, is a major threat to functioning and quality of life in PLWH.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The study by Penn et al in this issue brings needed attention to the psychosocial context of chronic pain in people living with HIV (PLWH) in the current treatment era. 17 As PLWH age and have normal life expectancy with antiretroviral therapy (ART), quality of life is now a focus. 9,15 Chronic pain, as highlighted by Penn et al, is a major threat to functioning and quality of life in PLWH.…”
mentioning
confidence: 99%
“…20 In their cross-sectional, questionnaire-based study, Penn et al found that perceptions of pain-related injustice (ie, appraisals of loss, unfairness, and blame) were associated with greater pain interference in PLWH; however, high levels of social support attenuated this association. 17 Although they did not directly assess stigma, the authors argue that stigma related to HIV and the pain itself, particularly when not attributed to clear pathology, might give rise to appraisals of one's situation as unjust. 17…”
mentioning
confidence: 99%
See 3 more Smart Citations